Commodity derivatives: Financialization and regulatory reform - Peter Gibbon (Danish Institute for International Studies (DIIS), 2013)
Commodity derivatives have been traded for well over a century, often stimulating calls for stricter regulation during periods of major commodity price inflation or deflation. The 2000s, when a sharp rise in commodity prices coincided with a spectacular rise in participation in derivatives markets by financial investors or speculators, were no exception. The coincidence of these events with the crash of 2008 led to the inclusion of commodity derivative regulation within the broader framework of new US and EU financial sector regulation. The paper reviews this sequence of events and their interconnections as well as the reforms themselves. Subsequently, it follows the trajectories both of derivative market financialization and regulatory reform up to mid-2013, showing a post-crash stabilization of market involvement by financial interests and the emergence of certain new regulatory directions.
Keywords: 300